Historical blocking: CN 2021-12-22 (China) - Voidly (Voidly Global Censorship Index, 2021)
CRITICAL severity censorship detected in China. Data sourced from ooni-historical-backfill.
Censorship Incident ID: CN-2021-0007. Severity: critical. Confidence: 98%